2012
DOI: 10.1891/1061-3749.20.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and Confirmatory Factor Analysis of the Decision Regret Scale in Recipients of Internal Cardioverter Defibrillators

Abstract: The Decision Regret Scale (DRS) is a five-item instrument that captures an individual’s regret associated with a healthcare decision. Cross-sectional data were collected from 109 cardiac patients who decided to receive an internal cardioverter defibrillator (ICD). Exploratory and confirmatory factor analyses, assessments of the internal reliability consistency (α = .86), and discriminant validity established the DRS as a reliable and valid measure of decision regret in ICD recipients. The DRS, a psychometrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…With respect to structural validity, the CFA confirmed a unidimensional structure of the DRS‐C similar to the DRS. Prior to our work, unidimensionality of the original DRS was also confirmed in internal cardioverter defibrillator recipients and people with cancer or patients with cancer receiving adjuvant chemotherapy . The internal consistency was very good and comparable to the one reported for the original DRS (0.81 to 0.84 for people with cancer or patients with cancer) and the one identified in the Japanese validation of the original DRS (0.85) .…”
Section: Discussionsupporting
confidence: 68%
“…With respect to structural validity, the CFA confirmed a unidimensional structure of the DRS‐C similar to the DRS. Prior to our work, unidimensionality of the original DRS was also confirmed in internal cardioverter defibrillator recipients and people with cancer or patients with cancer receiving adjuvant chemotherapy . The internal consistency was very good and comparable to the one reported for the original DRS (0.81 to 0.84 for people with cancer or patients with cancer) and the one identified in the Japanese validation of the original DRS (0.85) .…”
Section: Discussionsupporting
confidence: 68%
“…Our results indicate that the patients most likely to regret treatment are those with worse QoL, including physical status, presence of symptoms, and greater psychological distress. Other authors found that regret was greater in patients with heart disease with worse perceived physical health 30 , and regret was associated with depression, anxiety, and stress in women with breast cancer 31 . We did not find differences in regret by gender, age, educational level, or type of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…A study survey was developed to collect socio-demographics and medical history. We used the Situation-Specific Theory of Heart Failure Self-Care 7 (Figure 1) to select relevant concepts pertaining to the person (HF knowledge - DHFKS, 13 health literacy - S-TOFHLA, 14 depressive symptoms - CESD-10, 15,16,17 and Decision Regret scale 21,22 ) and the environment (social support - MOS, 18 ). These concepts are hypothesized to influence HF self-care (SCHFI 19,20 ), decision delay, and hospitalizations.…”
Section: Measurementmentioning
confidence: 99%
“…All study measurements have previously established reliability and validity. 1322 Medical variables such as New York Heart Association (NYHA) Class and Charleston Comorbidity Index were determined via self-report. Thirty day rehospitalization status was determined by participant self-report and medical chart review and decision delay was assessed via self-report.…”
Section: Measurementmentioning
confidence: 99%